A life cycle assessment of vegan dog food - Lena Jarosch; Vanessa Bach; Matthias Finkbeiner (Cleaner Environmental Systems, 2024)
Dog food accounts for 90% of the average dog's impact on climate change. Vegan dog food is one possible alternative. There are few studies evaluating its environmental impacts. The goals of this paper are to i) determine the environmental impacts and hotspots of wet vegan dog food, ii) compare results with average meat-based alternative and estimate global climate change potential of switching from meat-based to vegan dog food diet. A life cycle assessment was performed for a can of vegan dog food for the categories climate change, freshwater eutrophication, terrestrial acidification, smog, and land use. Each can had a carbon footprint of 0.4 kg CO2-eq., adding up to 443 kg CO2-eq over a dog's 15-year lifespan. A comparison with meat-based dog food showed reduction potentials in acidification by 50%, climate change by 37%, and smog by 18%, but higher impacts in land use by 97%, and eutrophication by almost 300% applying the assumptions by Pet Food Industry Federation. The results differ from other studies showing reductions in land use and eutrophication. Switching to a vegan diet can reduce GWP emissions by 340 kg CO2eq per year, while this could increase up to 6000 if high quality meat is fed.